Esophageal diverticulum exposed during endoscopic submucosal dissection of superficial cancer - Tanaka, Shinwa (World J Gastroenterol, 2015)
Endoscopic submucosal dissection (ESD) is now widely accepted as a strategy to treat superficial esophageal neoplasms. The rate of adverse events, such as perforation, has been decreasing with the improvement of devices and techniques. In this paper, we report a case of esophageal cancer that had a diverticulum under cancerous epithelium. The diverticulum was not detected during preoperative examination, and led to perforation during the ESD procedure. Our case shows that, although rare, some diverticula can exist underneath the mucosal surface without obvious depression. If there is any sign of hidden diverticula during ESD, surgeons should proceed with caution or, depending on the case, the procedure should be discontinued to avoid adverse events.